Inventory and Logistics Management for Imported Car Detailing Entrepreneurs (International Seven Journal of Multidisciplinary, 2023)
This article explores strategic inventory and logistics management practices tailored to entrepreneurs operating in the imported car detailing industry. Given the specificity of products and the international nature of sourcing, these businesses face unique challenges that demand precise planning and execution. The study highlights the importance of automated inventory systems, lean warehousing, Just-in-Time (JIT) principles, and the integration of logistics with customer service operations. It further discusses the role of sustainability, e-commerce globalization, and risk resilience, emphasizing the growing relevance of digital technologies such as artificial intelligence and IoT in enhancing operational efficiency. Ultimately, the article argues that mastering inventory and logistics not only supports day-to-day functionality but also strengthens long-term competitiveness in a demanding niche market.